2015
DOI: 10.1007/s00442-015-3377-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing coexisting plant extinction debt and colonization credit in a grassland–forest change gradient

Abstract: Changes in species richness along the ecological succession gradient may be strongly determined by coexisting extinction debts of species from the original habitats and colonization credits of those from the replacing habitats. The magnitude of these processes and their causes remain largely unknown. We explored the extinction debt and colonization credit for grassland and forest specialist plants, respectively, and the local and landscape factors associated to the richness of these species groups in a 50-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 45 publications
3
37
0
Order By: Relevance
“…Conversely, only few authors have explored the effects of habitat recovery on the assembly of plant-animal interactions (de la Peña et al, 2016). Recent formation and high isolation of habitat patches may result in time lags (namely, colonization credits) for some species, especially those with poor dispersal ability (Bagaria, Helm, Rodà, & Pino, 2015;Heiniger et al, 2014). Recent formation and high isolation of habitat patches may result in time lags (namely, colonization credits) for some species, especially those with poor dispersal ability (Bagaria, Helm, Rodà, & Pino, 2015;Heiniger et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, only few authors have explored the effects of habitat recovery on the assembly of plant-animal interactions (de la Peña et al, 2016). Recent formation and high isolation of habitat patches may result in time lags (namely, colonization credits) for some species, especially those with poor dispersal ability (Bagaria, Helm, Rodà, & Pino, 2015;Heiniger et al, 2014). Recent formation and high isolation of habitat patches may result in time lags (namely, colonization credits) for some species, especially those with poor dispersal ability (Bagaria, Helm, Rodà, & Pino, 2015;Heiniger et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Species richness and nestedness (although marginally) were affected by present connectivity, but not by past connectivity (Figure d,e), indicating that current immigration from surrounding habitats maintains high species richness and grassland specialist plants. In contrast to this result, time‐delayed responses to landscape change (Jackson & Sax, ) have been reported for species richness (Bagaria, Helm, Roda, & Pino, ; Helm et al, ; Koyanagi, Kusumoto, Yamamoto, Okubo, et al, ; Lindborg & Eriksson, ; Otsu, Iijima, Nagaike, Takuo, & Hoshino, ) and nested components (Koyanagi, Furukawa, & Osawa, ) of grassland plant communities. Cousins () found that time‐delayed response is detected in regions where contemporary landscapes retain >10% of traditional habitats.…”
Section: Discussionmentioning
confidence: 78%
“…Projected generalist plant dynamics indicate that the order of magnitude of relaxation times ranges from several centuries to near a millennium (Figure a). Previous studies about immigration credit reported smaller time lags, mainly decades or several centuries (Bagaria, Helm, Rodà, & Pino, ; Naaf & Kolk, ; Hautekèete et al., ). First, these differences could be explained by the extinction debt that slows down the use of the immigration credit in our study area in comparison to that of Naaf and Kolk () who concluded that the extinction debt was already paid.…”
Section: Discussionmentioning
confidence: 92%
“…; Bagaria et al. ; Hautekèete et al., ) without regard to the time needed to reach a novel equilibrium (i.e. the relaxation time).…”
Section: Discussionmentioning
confidence: 99%